Neuroimmunomodulatory Properties of Flavonoids and Derivates: A Potential Action as Adjuvants for the Treatment of Glioblastoma - Ravena Pereira do Nascimento; Balbino Lino dos Santos; Jéssika Alves Oliveira Amparo; Janaina Ribeiro Pereira Soares; Karina Costa da Silva; Monique Reis Santana; Áurea Maria Alves Nunes Almeida; Victor Diógenes Amaral da Silva; Maria de Fátima Dias Costa; Henning Ulrich; Vivaldo Moura-Neto; Giselle Pinto de Faria Lopes; et al. (MDPI AG, 2022)
Glioblastomas (GBMs) are tumors that have a high ability to migrate, invade and proliferate in the healthy tissue, what greatly impairs their treatment. These characteristics are associated with the complex microenvironment, formed by the perivascular niche, which is also composed of several stromal cells including astrocytes, microglia, fibroblasts, pericytes and endothelial cells, supporting tumor progression. Further microglia and macrophages associated with GBMs infiltrate the tumor. These innate immune cells are meant to participate in tumor surveillance and eradication, but they become compromised by GBM cells and exploited in the process. In this review we discuss the context of the GBM microenvironment together with the actions of flavonoids, which have attracted scientific attention due to their pharmacological properties as possible anti-tumor agents. Flavonoids act on a variety of signaling pathways, counteracting the invasion process. Luteolin and rutin inhibit NFκB activation, reducing IL-6 production. Fisetin promotes tumor apoptosis, while inhibiting ADAM expression, reducing invasion. Naringenin reduces tumor invasion by down-regulating metalloproteinases expression. Apigenin and rutin induce apoptosis in C6 cells increasing TNFα, while decreasing IL-10 production, denoting a shift from the immunosuppressive Th2 to the Th1 profile. Overall, flavonoids should be further exploited for glioma therapy.